Transmission of tuberculosis in high school students in Worcester, South Africa - Bunyasi, Erick (Department of Pathology, 2020)
Introduction Although adolescents have the highest force of Mycobacterium tuberculosis infection1 and rapidly increasing burden of tuberculosis (TB) disease through 10–19 years of age,2 there are few studies on adolescent Mycobacterium tuberculosis infection, transmission, and TB disease in the WHO African region. Adolescents in the high TB burden countries of Africa are therefore an important, but neglected risk group for global TB control efforts. Adolescents spend a considerable amount of their time in school classrooms, but there is paucity of data on classroom risk of Mycobacterium tuberculosis transmission. To the best of our knowledge, no published study has conducted measurement of air quality and air sampling for Mycobacterium tuberculosis DNA in school classrooms, a novel approach that may support targeted TB disease case–finding strategies which may be more efficient than symptom–based TB screening in the congregate school setting. The overall aims of this PhD project were: 1) To conduct a systematic review of adolescent latent TB infection (LTBI) and TB disease prevalence, and to examine the relationship between adolescent Mycobacterium tuberculosis infection and TB disease rates, in high TB burden African countries. 2) To describe temporal changes in prevalence of LTBI among adolescents living in a single TB endemic South African community, across two time periods spanning the decade 2005–2015. 3) To describe temporal changes in adolescent TB disease notification rates in the same community for the decade 2005–2015. 4) To determine classroom ventilation risk for Mycobacterium tuberculosis transmission in tandem with a pilot study of air sampling for Mycobacterium tuberculosis DNA; and to investigate the operational feasibility and yield of a pragmatic, symptom–based approach to TB disease surveillance in high schools. Methods To achieve Aim 1, we performed a bibliographic database search for studies conducted and published between 1990 and 2018 on prevalence of adolescent (10–19 years) LTBI and TB disease in high TB burden African countries. We calculated the ratio between the number of Mycobacterium tuberculosis infections based on Annual Risk of TB Infection (ARTI) estimates and the number of microbiologically–confirmed TB disease cases per year, and compared the observed ratio to the expected ratio of 8–12 published by Styblo et al.3 To achieve Aim 2, we collected adolescent LTBI (defined by positive QuantiFERON® –TB Gold In–Tube test) prevalence data from eight South African high schools, spanning the decade 2005–2015, from databases of an adolescent cohort study (2005–2007) and an adolescent vaccine trial (2014–2015). We used the two–sample test of equality of proportions to compare changes in LTBI prevalence over the two periods. To achieve Aim 3, we collected adolescent TB disease notification data from the same community (using an electronic tuberculosis disease register) for the decade 2005–2015 and we used the Mann–Kendall test to explore temporal changes in notification rates. To achieve Aim 4, we conducted a cross sectional study of 72 classrooms occupied by 1,836 high school learners, in addition to 7 comparator clinic spaces selected for high a priori risk of Mycobacterium tuberculosis transmission, and performed ventilation (carbon dioxide concentration) measurement to define spaces with high ventilation risk (>1,000 ppm) and ddPCR air sampling for Mycobacterium tuberculosis DNA, with active TB symptom screening among learners. Results 1) There is paucity of data on adolescent LTBI and TB disease prevalence in high TB burden African countries (1990–2018). Based on the limited available data, both LTBI (16%–55%)4–8 and TB disease prevalence rates are high (180–679 cases per 100,000),6–10 but corresponding infection–to–disease ratios are inconsistently low compared to that expected from Styblo's Rule.3 2) Overall adolescent LTBI prevalence remained high and relatively unchanged (44–49%) between 2005– 2015. 11 However, although average LTBI prevalence was unchanged in lower socio–economic quintile schools, prevalence increased in highest socio–economic quintile schools (from 20% to 38%).11 3) Adolescent TB disease notification rates fell 45% (662 to 361 per 100,000) in the same community over the same period. Despite this decrease, recent TB disease prevalence remains high and is three– fold higher in older (15–19 years) than younger (10–14 years) adolescents (566 vs. 151 per 100,000 in 2015). 4) More than one–third of 72 high school classrooms were inadequately ventilated and one–fifth of classrooms had evidence of airborne Mycobacterium tuberculosis DNA detected by ddPCR air sampling. The average risk of inhaling 1 Mycobacterium tuberculosis DNA copy was similar between clinics and classrooms. Across all classrooms the average risk of a classroom occupant inhaling 1 Mycobacterium tuberculosis DNA copy over 1 lesson (35 minutes) was 0.71%; and the estimated risk over 1 academic year was 100%. However, yield from symptom–based TB screening was low, consistent with the presence of undiagnosed subclinical TB cases and risk of ongoing transmission in the school setting. Conclusion Despite the encouraging decline in adolescent TB disease notification rates observed between 2005–2015 in the study area, adolescent LTBI prevalence remains high, consistent with ongoing medium–term transmission. The relatively high proportion of inadequately ventilated classrooms would place learners at high risk of Mycobacterium tuberculosis transmission if exposed to an infectious occupant. This risk appears material, given the proportion of classrooms with a positive ddPCR air filtrate sample and the estimated cumulative risk of inhaling of at least one copy of Mycobacterium tuberculosis DNA. The presence of previously undiagnosed TB cases among learners is inferred from our classroom ddPCR air sampling data, which further suggest that pragmatic school–based TB symptom screening is an inefficient surveillance strategy that likely missed learners with subclinical TB. Improved ventilation in school classrooms is a low–cost intervention that may reduce the risk of TB transmission in schools. New and more efficient targeted TB disease case–finding strategies are needed for congregate settings, including schools, in high TB burden countries. Based on our preliminary data, classroom ddPCR air sampling for Mycobacterium tuberculosis DNA appears feasible for this purpose, but requires further research to optimise diagnostic accuracy and demonstrate cost–effectiveness and public health value in high TB burden countries.